Analisis Ragam Bahasa Slogan pada Papan Reklame di Kota Padang (Kajian Sosiolinguistik) - Indriani, Nadia Eka Putri; Afnita (Imajeri: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
This research aims to provide an explanation of how slogans on billboards in Padang City are used and the different types of language used. This research used photographs as documentation. Qualitative descriptive method was used. The results show that slogans use simple and concise language. Most of the slogans do not change syntax and morphology. The aim is to help people remember the slogan. Slogans posted on billboards in Padang are mostly in Indonesian, most are in English, and some use both. Slogans also use regional dialects.